Evaluation of Cytotoxicity and Cytoprotection. Effects of Natural Toxins (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The lifestyle associated with good quality of food is well known for its widely recognized health benefits, especially when rich in bioactive compounds. Reduced risks of some types of cancer and other diseases have been associated with the adoption of such a diet, as have increased antioxidants, inhibitors of lipid peroxidation, decrease of pro-inflammatory cytokine production, etc. The focus of this Special Issue of Toxins was to gather advances related to the cytotoxicity of natural toxins and the potential for the cytoprotection of natural compounds present in food or plants. In this context, this Special Issue of Toxins comprises eight original contributions. Special attention is given to Fridericia chica (Bignoniaceae) leaves grown in Colombia, extract from Polygonum cuspidatum, Artemisia annua and coffee extracts against mycotoxins´ effects. Studies of mycotoxins in different animal and human cell lines are also presented for zearalenone, beauvericin, α-zearalenol and β-zearalenol, among others.